2021
DOI: 10.1002/ange.202107327
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Phosphorothioates Enter Cells by Thiol‐Mediated Uptake

Abstract: Oligonucleotide phosphorothioates (OPS) are DNA or RNA mimics where one phosphate oxygen is replaced by a sulfur atom. They have been shown to enter mammalian cells much more efficiently than non‐modified DNA. Thus, solving one of the key challenges with oligonucleotide technology, OPS became very useful in practice, with several FDA‐approved drugs on the market or in late clinical trials. However, the mechanism accounting for this facile cellular uptake is unknown. Here, we show that OPS enter cells by thiol‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Thus, the effects of hairpin structure on cytosolic penetration might be due to decreased overall association with the membrane, decreased efficiency of uptake into endosomes, decreased efficiency of escape from endosomes, or some combination of these factors. Matile and colleagues have recently suggested that PS‐modified oligonucleotides enter the cells through a “thiol‐mediated uptake” mechanism mediated by transient covalent interactions with thiols on cell surface proteins [56,57] . This model was inspired by prior work which showed that antisense oligonucleotides with phosphorothioate backbones interact with many cell‐surface proteins, most of them cysteine‐rich [3,15,16,58] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of hairpin structure on cytosolic penetration might be due to decreased overall association with the membrane, decreased efficiency of uptake into endosomes, decreased efficiency of escape from endosomes, or some combination of these factors. Matile and colleagues have recently suggested that PS‐modified oligonucleotides enter the cells through a “thiol‐mediated uptake” mechanism mediated by transient covalent interactions with thiols on cell surface proteins [56,57] . This model was inspired by prior work which showed that antisense oligonucleotides with phosphorothioate backbones interact with many cell‐surface proteins, most of them cysteine‐rich [3,15,16,58] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, disulfide reshuffling has been documented at the surface mammalian cells in numerous studies. [28][29][30]34 For bacteria, such reports are scant and in fact antibiotics acting in the cytoplasm were inactivated via their conversion to disulfide-containing derivatives, possibly suggesting conjugation to the bacterial cell surface and thereby arrested drug cell entry. 31 In recent studies, Shchelik and Gademann 51,52 observed that the disulfide containing derivatives of vancomycin and cephalosporin were superior to the parent antibiotic molecules, although no mechanism for the involvement of the disulfide functionality was provided to explain the enhanced drug efficacy of the newly synthesized compounds.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible mechanism can involve the thiol groups nested at the cell surface. For mammalian cells, exofacial sulfhydryls have become a highly important player in drug delivery at cell surfaces 39 and/or to the cell interior 28,29,34 . Thiols are also abundant on bacterial cells, [31][32][33] making it possible that interaction of ADCs with the cell surface ensues a thiol-disulfide exchange and release of the active drug.…”
Section: Antimicrobial Efficacy Of Adcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from elucidation of the charge transfer processes between backbone and base studied here, DNA model systems (nucleotides and oligonucleotides of defined sequences) with either phosphorothioate or phosphorodithioate substitutions are widely employed as antisense nucleotides, owing to their good cellular uptake due to better nuclease stability. In fact, phosphorothioation has been one of the first backbone modifications introduced . It is noteworthy that either phosphorothioate or phosphorodithioate modification minimally affects the DNA geometry and base stacking. ,, Furthermore, phosphorothioation of the backbone is known to occur in nature and has been observed in bacteria and archea. , …”
Section: Introductionmentioning
confidence: 99%